The Word and Time: Historical Reality in the Prose of Valentin Pikul (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article examines the historical themes in the works of the writer, his desire to convey the patriotic feelings of the Russian people through artistic imagery. In his novels, there is a clear contrast between positive and negative characters, the struggle between good and evil, and the conflict between the sense of duty to the Motherland and betrayal. These elements create a vivid picture of the historical era and allow the reader to dive deeper into the events of the past.